Analysis Of Consumer Preferences In Buying Broiler Chicken Meat - Achmad Faqih; Siti Aisyah; Hanif Farihin Sya’bani; Rifki Ahmad Ramadhan; Taufik Rahman Darmadi; Panji Maulana Yusuf (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
In general, consumers in buying a product are closely related to the attributes attached to the product concerned. This is because these attributes will cause preference. Therefore, knowledge of attributes and preferences becomes very important, especially for manufacturers or traders. This study aims to: 1) find out the attributes of chicken meat that are consumer preferences and 2) find out the attributes that consumers consider most in buying broiler chicken meat. The research design used in this study was using quantitative descriptive methods with survey research methods. The population used is consumers who buy broiler chicken meat at the Pasar Minggu Traditional Market, Palimanan District, Cirebon Regency. The attributes studied in broiler chicken meat are the price of meat, meat parts, meat texture, and meat color. The number of samples used was 100 respondents with a sampling technique using accidental sampling. The study was conducted in July-August 2022. Data analysis techniques using chi square test and fishbein multiattribute analysis. The results showed that 1) there are differences in consumer preferences for the attributes that exist in broiler chicken meat. The attributes of broiler chicken meat that become consumer preferences are the price of meat, meat parts, meat texture, and meat color. The attributes of broiler chicken meat that consumers like are the price of meat IDR 30,000.-, the broiler chicken meat part is breast, the texture of broiler chicken meat is chewy texture, and the color of broiler chicken meat is yellowish white, 2) the attributes most considered by consumers in buying broiler chicken meat consecutively ranging from the highest to the lowest are the price of meat, meat color, texture of meat, and parts of meat